2007
DOI: 10.1109/iembs.2007.4353617
|View full text |Cite
|
Sign up to set email alerts
|

A Medical Texture Local Binary Pattern For TRUS Prostate Segmentation

Abstract: Prostate cancer diagnosis and treatment rely on segmentation of Transrectal Ultrasound (TRUS) prostate images. This is a challenging and difficult task dut to weak prostate boundaries, speckle noise and the short range of gray levels. Advances in digital imaging techniques have made it possible the acquisition of large volumes of TRUS prostate images so that there is considerable demand for automated segmentation systems. Local Binary Pattern (LBP) has been used for texture segmentation and analysis. Despite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Texture analysis has also been used to identify unique pathology on multi-modality images of cancer patients. Using the local binary operator to analyse the weak underlying textures found in transrectal ultrasound images of the prostate, Kachouie and Fieguth demonstrated that the approach was suitable for segmentation of the prostate (Kachouie & Fieguth, 2007). In another cancer-related study of 48 normal images and 58 cancer images of the colon, Esgiar et al, demonstrated that by adding a fractal feature to traditional statistical features the sensitivity of the classification improved (Esgiar et al, 2002).…”
Section: Statistical Approaches For Texture Analysismentioning
confidence: 98%
“…Texture analysis has also been used to identify unique pathology on multi-modality images of cancer patients. Using the local binary operator to analyse the weak underlying textures found in transrectal ultrasound images of the prostate, Kachouie and Fieguth demonstrated that the approach was suitable for segmentation of the prostate (Kachouie & Fieguth, 2007). In another cancer-related study of 48 normal images and 58 cancer images of the colon, Esgiar et al, demonstrated that by adding a fractal feature to traditional statistical features the sensitivity of the classification improved (Esgiar et al, 2002).…”
Section: Statistical Approaches For Texture Analysismentioning
confidence: 98%
“…Rafiee et al [50] Appearance Statistical Mohamed et al [68] Appearance Statistical Song et al [75] Shape and appearance Graph-theoretic framework Liu et al [36] Shape Deformable ellipse Segmentation and clustering Kachouie and Fieguth [63] and Kachouie et al [35] Appearance A medical texture local binary pattern operator Richard et al [60] Appearance Law's mask Classification…”
Section: Asmmentioning
confidence: 99%
“…Segmentation is applied to extract the prostate [47,50,63] and to describe its zonal anatomy to permit data reduction and the application of different analysis algorithms based on the considered region.…”
Section: Diagnosis and Cancer Stagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study using the local binary pattern (LBP) operator for texture classification, Kachouie and Fieguth [12] demonstrated that the approach was sensitive to the weak underlying textures present in transrectal ultrasound (TRUS) prostate images. Furthermore, the authors demonstrated that the approach had the necessary discriminative attributes for segmentation of the prostate.…”
Section: Texture Analysismentioning
confidence: 99%